2017
DOI: 10.1002/hbm.23848
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the sequence of brain events in response to disgusting food

Abstract: Warning signals indicating that a food is potentially dangerous may evoke a response that is not limited to the feeling of disgust. We investigated the sequence of brain events in response to visual representations of disgusting food using a dynamic image analysis. Functional MRI was acquired in 30 healthy subjects while they were watching a movie showing disgusting food scenes interspersed with the scenes of appetizing food. Imaging analysis included the identification of the global brain response and the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
2
31
1
Order By: Relevance
“…An exceptional early study identified regions of the brain that are involved in the initial stages of emotion elicitation during listening to a narrative ( Sabatinelli et al, 2006 ). More recently, movie clips of disgusting vs. appetizing food were found to elicit a cascade of brain events from the orbitofrontal cortex and visual cortices to the periaqueductal gray matter, amygdala, and insula, finally reaching the cerebellum and DMN structures ( Pujol et al, 2018 ). These findings suggest that midline structures, which are central to emotion classification ( Saarimäki et al, 2016 ), are involved in the final stages of emotions’ elicitation and maintenance.…”
Section: Feature Films In Non-invasive Neuroimaging Studies Of Emotiomentioning
confidence: 99%
“…An exceptional early study identified regions of the brain that are involved in the initial stages of emotion elicitation during listening to a narrative ( Sabatinelli et al, 2006 ). More recently, movie clips of disgusting vs. appetizing food were found to elicit a cascade of brain events from the orbitofrontal cortex and visual cortices to the periaqueductal gray matter, amygdala, and insula, finally reaching the cerebellum and DMN structures ( Pujol et al, 2018 ). These findings suggest that midline structures, which are central to emotion classification ( Saarimäki et al, 2016 ), are involved in the final stages of emotions’ elicitation and maintenance.…”
Section: Feature Films In Non-invasive Neuroimaging Studies Of Emotiomentioning
confidence: 99%
“…Importantly, a neuroimaging study by Basile et al (2011) found that the induction of deontological guilt increased activation of brain areas implicated in the emotion of disgust, such as the insula (Pujol et al, 2018), whereas altruistic guilt elicited activation in the theory of mind network, particularly in medial prefrontal brain areas. Taken together, these studies suggest that the Lady Macbeth effect may be more strictly connected with deontological rather than altruistic guilt.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study reported that increased variability of a subnetwork formed by the amygdala and the hippocampus correlated with worsening mood and depression ( Kirkby et al, 2018 ). For disgust, a recent study by Pujol et al (2018) found the involvement of the hippocampus in response to disgusting food, and another experiment ( Blanco-Hinojo et al, 2019 ) showed abnormal responses to disgusting food inside the hippocampus of individuals affected by Prader–Willi syndrome when compared to controls. We might speculate that the patient might have performed poorly in detecting sad and disgusting scenes in the attribution task because a damage of the hippocampus (for disgust) and of the amygdala–hippocampus circuit (for sadness) could have led also to mild deficits in processing sad and disgusting scenes.…”
Section: Discussionmentioning
confidence: 98%